OPTIMIZATION OF MILK PROCESSING PROCESSES AND ANALYSIS OF OBTAINED SOLUTIONS - Jandrić, Mersida; Vico, Grujica; Savić, Željko (Economics of Agriculture, 2024)
This study focuses on the analysis of optimization and sensitivity in dairy production, utilizing linear programming to achieve an optimal production structure and maximize net income. The model identifies key products with the highest revenues and those having the greatest impact on overall revenue and costs. Sensitivity analysis reveals which products are most sensitive to price changes and how these changes affect production structures, providing valuable insights for dairy management in pricing strategies and future investments. Additionally, the research opens opportunities for further improvements and exploring new market avenues and product diversification in the dairy industry.